EVALUATION OF THE ANTI-INFLAMMATORY ACTIVITY OF THE LINIMENT FROM THE LEAF EXTRACT OF VITEXNEGUNDO FAMILY VERBENACEAE - Abuan, Richelle G.; Cruz, Jonas Preposi; Colet, Paolo C. (European Scientific Journal, ESJ, 2014)
This study was conducted to evaluate the anti-inflammatory activity of the liniment from the leaf extract of Vitexnegundo family Verbenaceae.The leaves were extracted using Soxhlet apparatus. In-vitro protein stabilization test were done using the different concentrations of the leaf extract, 100%, 75%, 50%, and 25% and were used to treat the proteins in the albumin solution. The twenty five percent (25%) concentration exhibited the greatest anti-inflammatory reading based on the highest transmittance,a liniment was formulated using alcohol and oil as a base. The alcohol-based and oil-based liniments were tested using spectrophotometric analysis to determine if there was any significant difference on their anti-inflammatory action. Sensitivity test was also done using Patch Test and Scratch Test.After performing all the tests, the researchers concluded that the leaf extract has the ability to stabilize albumin and delay the onset of visible signs of denaturation making it less turbid and therefore increase transmittance reading, which indicates its effectiveness as a potential anti-inflammatory agent.